Analisis Determinan Perilaku Donasi Masyarakat pada Lembaga Filantropi Islam di Kota Banda Aceh - Syarif Hidayatullah; Hafas Furqani; Muhammad Zulhilmi (Jurnal Ekonomi Manajemen dan Sekretari, 2024)
Philanthropic organizations play a vital role in Indonesia by providing assistance to those in need, including the poor, dhuafa, and disaster victims. However, in 2022, one Islamic philanthropic organization in Indonesia was involved in a case of fund misappropriation, raising concerns about potential ripple effects on other institutions. This study examines the influence of credibility, brand awareness, and financial literacy on public interest in donating to philanthropic institutions in Banda Aceh. Using a quantitative approach, this research employs linear regression analysis as the primary analytical tool. A total of 100 respondents were selected as samples, determined through Cochran's formula and a nonprobability sampling method. The findings indicate that credibility, brand awareness, and financial literacy positively impact the public's interest in donating to Islamic philanthropic institutions in Banda Aceh. Collectively, these factors significantly influence the intention to donate among residents of Banda Aceh.